PHYTODIVERSITY AND PECULIARITIES OF RADIOACTIVE CONTAMINATION OF HERBALS AND OTHER ECONOMICALLY VALUABLE PLANT TYPES OF CHECHERSK DISTRICT OF GOMEL REGION BORDERING BRYANSK REGION OF RUSSIA - L. M. Sapegin; N. M. Dajneko; S. F. Timofeev (Радиационная гигиена)
255 plant (herbals and economically valuable plants) and 24 soil samples were taken from 4 investigated sites of Chechersk district for radiological analysis. The plants are presented by 33 species of 31 genera and 26 families. The rest 23 families included 1 species (3,0%) each. There were 6 (18,2%) tree species, 5 (15,1%) shrubs and 1 (3,0%) species of sub shrubs, 21 (63,6% ) species of grasses. Exceeding of 137Cs permissible concentration was found out for 21 (48,8%) of 51 taken plant samples. Strontium accumulation changed from 343 Bk/kg to 14 Bk/kg. The research has shown that most part of radionuclides remain in the surface soil layers, which constitutes certain danger. Moreover 90Sr migration in soil takes place much quicker than 137Cs. All these facts show that the use of herbals and other economically valuable plants from the studied sites is possible only under compulsory radiological control.